Science resource inequalities viewed as less wrong when girls are disadvantaged. Issue 1 (8th August 2022) - Sims, Riley N.; Burkholder, Amanda R.; Killen, Melanie
Abstract: In response to some resource inequalities, children give priority to moral concerns. Yet, in others, children show ingroup preferences in their evaluations and resource allocations. The present study built upon this knowledge by investigating children's and young adults' ( N = 144; 5–6‐year‐olds, M age = 5.83, SD age = .97; 9–11‐year‐olds, M age = 10.74, SD age = .68; and young adults, M age = 19.92, SD age = 1.10) evaluations and allocation decisions in a science inequality context. Participants viewed vignettes in which male and female groups received unequal amounts of science supplies, then evaluated the acceptability of the resource inequalities, allocated new boxes of science supplies between the groups, and provided justifications for their choices. Results revealed both children and young adults evaluated inequalities of science resources less negatively when girls were disadvantaged than when boys were disadvantaged. Further, 5‐ to 6‐year‐old participants and male participants rectified science resource inequalities to a greater extent when the inequality disadvantaged boys compared to when it disadvantaged girls. Generally, participants who used moral reasoning to justify their responses negatively evaluated and rectified the resource inequalities, whereas participants who used group‐focused reasoning positively evaluated and perpetuated the inequalities, though some age and participant gender findings emerged. Together, these findings reveal subtle gender biases that may contribute to perpetuating gender‐based science inequalities both in childhood and adulthood.